2014
DOI: 10.2169/internalmedicine.53.2743
|View full text |Cite
|
Sign up to set email alerts
|

Iron-deficiency Anemia Caused by a Proton Pump Inhibitor

Abstract: A 59-year-old man was orally administered rabeprazole, a proton pump inhibitor (PPI), for gastroesophageal reflux disease, after which he gradually developed iron-deficiency anemia. The anemia did not improve following the administration of ferrous fumarate, and endoscopic screening of the entire gastrointestinal tract, including the small intestine, did not reveal any findings indicating the cause of the anemia. The patient was then switched from rabeprazole to famotidine and the anemia was cured within three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 14 publications
0
21
1
Order By: Relevance
“…The Naranjo Adverse Drug Reaction Probability Scale and the Horn and Hansten Drug Interaction Probability Scale are both suggestive of an association between long-term PPI use and the observed iron deficiency anemia (scores of 5 and 6, respectively); however, the patient’s untimely death prevented confirmatory follow-up data from being obtained to confirm long-term PPI use as the culprit. Repeat lab work 3 months after cessation of omeprazole was planned to confirm recovery, as occurred in cases previously described [3], [5]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Naranjo Adverse Drug Reaction Probability Scale and the Horn and Hansten Drug Interaction Probability Scale are both suggestive of an association between long-term PPI use and the observed iron deficiency anemia (scores of 5 and 6, respectively); however, the patient’s untimely death prevented confirmatory follow-up data from being obtained to confirm long-term PPI use as the culprit. Repeat lab work 3 months after cessation of omeprazole was planned to confirm recovery, as occurred in cases previously described [3], [5]…”
Section: Discussionmentioning
confidence: 99%
“…There are 2 types of dietary iron: (1) the heme type derived from animal blood and muscle and (2) the more common nonheme type derived from plants, fruits, vegetables, grains, and nuts. Accounting for ~10% of the Western diet, the heme type is absorbed independently of gastric pH, whereas the nonheme component requires an acidic pH for absorption 3 . There are few case reports of iron deficiency induced by long-term omeprazole use and the effect of omeprazole on iron replacement therapy [3], [4], [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, PPI rarely cause clinically significant iron deficiency anemia. [7][8][9] To our knowledge, this is the first report of PPI-induced iron deficiency anemia that was severe enough to warrant a blood transfusion. Both atrophic gastritis and lansoprazole might have acted synergistically to decrease iron absorption, which resulted in anemia.…”
Section: Dear Editormentioning
confidence: 99%
“…Studies have shown that the problem ceases when PPI therapy is discontinued or replaced by the use of an H 2 ‐receptor antagonist , but treatment of ID in situations in which continued PPI therapy is required has been poorly studied. Intravenous iron therapy should be avoided.…”
mentioning
confidence: 99%